Hyperinflammatory State and Low T1 Adaptive Immune Response in Severe and Critical Acute COVID-19 Patients - Garcia-Gasalla, Mercedes; Berman-Riu, María; Pons, Jaime; Rodríguez, Adrián; Iglesias, Amanda; Martínez-Pomar, Natalia; Llompart-Alabern, Isabel; Riera, Melchor; Ferré Beltrán, Adrián; Figueras-Castilla, Albert; Murillas, Javier; Ferrer, Joana M. (Frontiers in Medicine, 2022)
Abstract Background: A better understanding of COVID-19 immunopathology is needed to identify the most vulnerable patients and improve treatment options. Objective: We aimed to identify immune system cell populations, cytokines, and inflammatory markers related to severity in COVID-19. Methods: 139 hospitalized patients with COVID-19 ―58 mild/moderate and 81 severe/critical ― and 74 recovered patients were included in a prospective longitudinal study. Clinical data and blood samples were obtained on admission for laboratory markers, cytokines, and lymphocyte subsets study. In the recovered patients, lymphocyte subsets were analysed 8-12 weeks after discharge. Results: A National Early Warning Score 2 >2 (OR:41.4; CI:10.3-167.0), ferritin >583 pg/mL (OR:16.3; CI: 3.8-69.9), neutrophil/lymphocyte ratio >3 (OR: 3.5; CI: 1.0-12.0), sIL-2rα (sCD25) >512 pg/mL (OR: 3.3; CI: 1.4-7.9), IL-1Ra >94 pg/mL (OR: 3.2; IC: 1.4-7.3), and IL-18 >125 pg/mL (OR: 2.4; CI: 1.1-5.0) were associated with severe/critical COVID-19 in the multivariate models used. Lower absolute values of CD3, CD4, CD8, and CD19 lymphocytes together with higher frequencies of NK cells, a CD4 and CD8 activated (CD38+HLA-DR+) memory T cell and effector memory CD45RA+ (EMRA) phenotype, and lower T regulatory cell frequencies were found in severe/critical patients relative to mild/moderate and recovered COVID-19 patients. A significant reduction in Th1, Tfh1, and Tc1 with higher Th2, Tfh2, Tc2, and plasma cell frequencies was found in the most severe cases. Conclusion: A characteristic hyperinflammatory state with significantly elevated neutrophil/lymphocyte ratio and ferritin, IL-1Ra, sIL-2rα, and IL-18 levels together with a “low T1 lymphocyte signature” was found in severe/critical COVID-19 patients.